Loss of the RNA-binding protein TACO1 causes late-onset mitochondrial dysfunction in mice - Tara R. Richman (Nature Portfolio, 2016)
Mutations in the translational activator of cytochrome c oxidase subunit I (TACO1) causes cytochrome c oxidase deficiency and Leigh Syndrome in patients. Here, the authors characterize mice with a mutation that causes lack of TACO1 expression, identifying a mouse model that could be useful for preclinical trials.